Expression profiles and associations of adiponectin and adiponectin receptors with intramuscular fat in Tibetan chicken. Issue 2 (4th March 2017) - Zhang, R.; Lin, Y.; Zhi, L.; Liao, H.; Zuo, L.; Li, Z.; Xu, Y.
ABSTRACT: 1. Adiponectin and its receptors (ADIPOR1 and ADIPOR2) are novel endocrine systems that act at various levels to modulate glucose and lipid metabolism. This study was designed to investigate the spatial expression of adiponectin, ADIPOR1 and ADIPOR2 genes in various tissues in Tibetan chicken. The temporal expression of adiponectin and its receptor mRNAs were also studied in adipose tissue, breast muscle and thigh muscle and the correlations of the levels of adiponectin, ADIPOR1 and ADIPOR2 mRNA with the contents of intramuscular fat in breast muscle and thigh muscle of Tibetan chicken were determined. 2. Quantitative real-time PCR detected chicken adiponectin, ADIPOR1 and ADIPOR2 mRNA transcripts in heart, liver, spleen, lung, kidney, skeletal muscle and adipose tissue. 3. Adipose tissue contained the highest amount of adiponectin mRNA followed by the kidney and liver. The expression levels of ADIPOR1 mRNA were significantly higher in adipose tissue, lung and spleen, and adipose tissue exhibited significantly higher levels of ADIPOR2 mRNA followed by the spleen and lung compared with other tissues. 4. Temporal expression profiles of adiponectin, ADIPOR1 and ADIPOR2 mRNA showed gender differences in adipose tissue and skeletal muscle at certain ages. In adipose tissue, adiponectin mRNA was higher in 154-d-old females and ADIPOR1 mRNA was higher in 154-d-old males: Adiponectin and ADIPOR2 mRNA were higher, and ADIPOR1 mRNA was lower, in thigh muscle in female compared with male chickens. 5. The correlation data showed that, except for adiponectin mRNA, the levels of ADIPOR1 and ADIPOR2 mRNA in thigh muscle of males were significantly positively correlated with IMF ( r = 0.206 for the ADIPOR1 gene and r = 0.676 for the ADIPOR2 gene). 6. Taken together, it was concluded that adiponectin and the ADIPOR1 and ADIPOR2 genes are ubiquitously expressed in various tissues of Tibetan chicken and the expression of the adiponectin system is gender-dependant at certain ages in adipose tissue and skeletal muscle.